The cybernetic brain : sketches of another future - Pickering, Andrew, 1948- (University of Chicago Press, 2010)
"Cybernetics is often thought of as a grim military or industrial science of control. But as Andrew Pickering reveals in this beguiling book, a much more lively and experimental strain of cybernetics can be traced from the 1940s to the present." "The Cybernetic Brain explores a largely forgotten group of British thinkers, including Grey Walter, Ross Ashby, Gregory Bateson, R.D. Laing, Stafford Beer, and Gordon Pask, and their singular work in a dazzling array of fields. Psychiatry, engineering, management, politics, music, architecture, education, tantric yoga, the Beats, and the sixties counterculture all come into play as Pickering follows the history of cybernetics' impact on the world, from contemporary robotics and complexity theory to the Chilean economy under Salvador Allende." "What underpins this history, Pickering contends, is a shared but unconventional vision of the world as ultimately unknowable, a place where genuine novelty is always emerging. And thus, Pickering avers, the history of cybernetics provides us with an imaginative model of open-ended experimentation in stark opposition to the modern urge to achieve domination over nature and each other"--Jacket.